Assessment of women food vending and local soap making micro enterprises in Temeke Municipal: A Costs Benefit Analysis approach - Shimba, Christina; Luvinga, Kepha; Kilasara, Simon Augustine (Advances in Social Sciences Research Journal, 2019)
This paper was designed to assess the contribution of women entrepreneurship in improving household livelihood at Temeke municipal council in Dar es salaam region, specifically the study aimed to identify the types and attributes, analyse sustainability of the selected enterprises and assess the contribution of women enterprises to household livelihood in the study area. A sample of 60 women were selected randomly from a list of women entrepreneurs' groups dealing with food vending (40) and local soap making who were 20. Data were collected using structured interview and were coded and entered into computer software. Cost benefit analysis and Sustainable Livelihood Index were used to analyse the viability and contribution of food vending and local soap making enterprises. Results show that the two enterprises were viable, but local soap making is more viable than food vending. Thus it is concluded that innovative enterprises are sustainable and can improve the household livelihood. The paper recommends that the government and other stakeholders should facilitate and motivate women to embark more in innovative enterprises for enhancing their livelihoods.